PENGGUNAAN TOILET BERSIH DAN SEHAT UNTUK MENINGKATKAN SANITASI LINGKUNGAN - Manggul, Makrina Sedista; Firana Enes, Marlina; Viven, Ordilia; Parus, Agnesia Nimat (LPPM Univ. Ibn Khaldun Bogor, 2021)
ABSTRACT Background: toilet is a basic facility or one of the most vital sanitation facilities and must exist in every household. In addition to being available in adequate quantities, toilets must also be clean, comfortable and suitable for use. Toilets can be useful as a place to dispose of human waste (feces), where feces are seen as objects that can endanger health if not handled seriously because feces can be used as a medium for disease transmission, especially diarrheal diseases. Sanitation is an effort made to avoid disease and human behavior who do not have clean and healthy living habits in order to improve and maintain good health. Analysis and situation: from the observations of the team with the village government and health workers, there are still many people in Golo Ngawan village, Sambi Rampas district, East Manggarai Regency who do not have standard and clean toilets, such as many toilets that do not have roofs and the walls use bamboo or cloth, do not use toilets , does not provide water for hand washing, does not provide a trash can and does not create a drainage flow. Problem: many people do not realize and understand how important it is to use toilets with clean and healthy sanitation standards so that they do not cause environmental pollution and spread disease to the community. Conclusion: can increase public awareness in the use of clean toilets as an effort to improve healthy environmental sanitation. Keywords: Environmental Sanitation, clean toilet